The Risk Element in Satellite insurance Contract - Sidqi Mohammed Amin Eesa; Kamaran mohammed qadir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
One of the established facts in the field of insurance is that insurance focuses on covering or guaranteeing a specific risk that represented in the loss of a financial value or the advent of a certain term and, in general, the occurrence of a future event, in return for bearing financial burdens represented in paying premiums periodically to the insured. If the risk is occurred, then the insurer must pay the sum insured to the insured. Based on this fact, the insured (risk) constitutes an essential element of the insurance contract and it has a more special importance in the field of satellite insurance contracts. The risk, as an essential element of the insurance contract, must meet several conditions in order to be valid to be the subject of the insurance contract: It must be a potential event, and it must be a future event, then it must not be related to the will of one of the parties to the contract, and finally it must be legitimate. Compared to other fields of insurance, the risk in the field of satellite insurance has more forms and types, and each of these types may be individually or with others subject to the insurance contract, as the contract does not necessarily cover all types of risks.